The ice thickness distribution of Flask Glacier, Antarctic Peninsula, determined by combining radio-echo soundings, surface velocity data and flow modelling - Farinotti, Daniel; Corr, Hugh; Gudmundsson, Hilmar (Annals of Glaciology, 2013)
An interpolated bedrock topography is presented for Flask Glacier, one of the tributaries of the remnant part of the Larsen B ice shelf, Antarctic Peninsula. The ice thickness distribution is derived by combining direct but sparse measurements from airborne radio-echo soundings with indirect estimates obtained from ice-flow modelling. The ice-flow model is applied to a series of transverse profiles, and a first estimate of the bedrock is iteratively adjusted until agreement between modelled and measured surface velocities is achieved. The adjusted bedrock is then used to reinterpret the radio-echo soundings, and the recovered information used to further improve the estimate of the bedrock itself. The ice flux along the glacier center line provides an additional and independent constraint on the ice thickness. The resulting bedrock topography reveals a glacier bed situated mainly below sea level with sections having retrograde slope. The total ice volume of 120±15 km3 for the considered area of 215 km2 corresponds to an average ice thickness of 560±70 m.